Appunti sul Porfirio delle Operette morali e dell’ultimo Luzi: dall’“estrema lezione” al “ragazzo di Recanati” - Battistel, Lucia (Rivista Internazionale di Studi Leopardiani, 2024)
Porphyry, who acts as a spokesman, in the homonymous Dialogo, of a young Leopardi, and as a counterpoint to his Neoplatonic master Plotinus behind who hides a more mature Leopardi, is welcomed and rethought in Mario Luzi’s last poetry. As a new Plotinus, Luzi conveys a “final lesson” of humanitas to the “Recanati’s youngster”. By doing so, he rehabilitates and reconciles Leopardi’s philosophy with his own system of thought.